Immobilization kinetics of CMCase and β-glucosidase from Aspergillus niger in calcium alginate beads - GARG, NEELIMA; KUMAR, DEVENDRA; YADAV, KAUSHLESH K; M, MUTHUKUMAR (The Indian Journal of Agricultural Sciences, 2015)
Carboxymethyl cellulase (CMCase) and Î²-glucosidase were produced by Aspergillus niger using mango peel residue as substrate and immobilized on calcium alginate beads through entrapment technique. The catalytic properties of the immobilized CMCase and β-glucosidase were compared to free enzyme. The enzyme efficiency of the immobilized CMCase and β-glucosidase were found to be 89.52 and 86.61%, respectively. Maximum immobilization efficiency was achieved on beads formed by 5% (m/v) of sodium alginate and bead size of 2 mm and 1.5 mm, for CMCase and β-glucosidase, respectively. The immobilized enzyme showed higher stability over a wider pH and temperature range. Metal ions, viz. Cu2+, Mo2+, Mn2+, Ca2+, B3+, Zn2+, Mg2+ and Fe2+ showed positive effect for immobilized β-glucosidase activity, while Mg2+ on immobilized CMCase activity. The immobilized enzymes could express 20-25% relative enzyme activity even after 4th repeated use. Immobilization improved the thermal stability over the free enzyme and affected the enzyme kinetic constants, viz. KM, Vmax and activation energy.